What is Criminal Restitution? - Lollar, Cortney E. (2014)
A new form of restitution has become a core aspect of criminal punishment. Courts now order defendants to compensate victims for an increasingly broad category of losses, including emotional and psychological losses and losses for which the defendant was not found guilty. Criminal restitution therefore moves far beyond its traditional purpose of disgorging a defendant's ill-gotten gains. Instead, restitution has become a mechanism of imposing additional punishment. Courts, however, have failed to recognize the punitive nature of restitution and thus enter restitution orders without regard to the constitutional protections that normally attach to criminal proceedings. This Article deploys a novel definition of punishment to situate restitution alongside other forms of punishment. As with other forms of punishment, courts impose restitution subsequent to a criminal allegation, pursuant to a statute motivated by morally condemnatory intent, and resulting in a substantial deprivation or obligation. Because restitution has become a form of punishment, this Article argues that judges should recognize criminal restitution for what it is—victim compensation imposed at the state's request as condemnation for a moral wrong—and extend to defendants in restitution proceedings all the constitutional protections they enjoy in other criminal proceedings. This means submitting restitution to a jury for determination pursuant to the Sixth Amendment, and subjecting it to the excessive fines analysis of the Eighth Amendment